Use of Triple Microcatheters for Endovascular Treatment of Wide-Necked Intracranial Aneurysms: A Single Center Experience - Cho, Young Dae (Korean J Radiol, 2015)
OBJECTIVE: The dual microcatheter technique is common practice for coil embolization of a wide-necked aneurysm, due to safety and efficacy. However, technical limitations of some complex configurations may necessitate additional microcatheters to bolster coil stability, compact the coil, or for protection. Described herein is a triple microcatheter technique for endovascular management of wide-necked intracranial aneurysms. MATERIALS AND METHODS: Data accruing prospectively between January 2006 and October 2014 on simultaneously executed triple microcatheter coil embolization procedures done in 38 saccular aneurysms were reviewed. Clinical and morphological outcomes were assessed, with emphasis on technical aspects of treatment. RESULTS: The triple microcatheter technique was successfully applied to all 38 saccular aneurysms, involving the posterior communicating artery (n = 13), the middle cerebral artery (n = 10), the basilar tip (n = 7), the anterior cerebral artery (n = 5), and the internal carotid artery (n = 3). Stent protection was added in four patients and balloon remodeling in one. Dual microcatheters (n = 24) were usually deployed to deliver the coil within sacs of aneurysms, with the additional microcatheter used for protection. Otherwise, triple microcatheters were deployed for coil delivery (n = 11) or coils were delivered via a single microcatheter, with dual microcatheters deployed for protection (n = 3). Successful occlusion of aneurysms was achieved in 89.5% of cases, with no procedure-related morbidity or mortality. Stable occlusion was maintained in 72.2% (26/36) of the aneurysms at the final follow-up (mean interval, 30.2 ± 22.7 months). CONCLUSION: The outcomes of this limited study suggest that the triple microcatheter technique may be an effective and safe therapeutic option for wide-necked aneurysms, using technical strategies tailored to complex angio-anatomic configurations.